Dimensi Sosial Tawa menurut Henri Bergson: Makna dan Fungsi Tawa dalam Interaksi Sosial - Sumboko, Agung; Nugroho, Wahyu Budi; Kamajaya, Gede (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2021)
This research is intended to explain Henri Bergson’s thought about laughter within the framework of sociological studies and analyze the contextualization social dimension of laughter related to its meaning and function in social interaction. In Henri Bergson’s treatise, the term comic has a funny meaning or ridiculous. Someone whose movements are comic is someone whose behavior contains the elements of mechanism and automatism, the movements without life. Laughter is used as a correction tool to punish those who act comic. Henri Bergson’s thoughts within the framework of sociological studies are included in the classification of the social definition paradigms and are elaborated in the theory of symbolic interactionism. A comedy can give a lot of information about comic, a comedy deliberately creates mistakes by overturning logic in both scenes or dialogues. The comedy connoisseurs enjoy and laugh with comedies that feature humans making certain mistakes. Keywords: Laughter, humor, comic, Henri Bergson